O-GlcNAcylation inhibition redirects the response of colon cancer cells to chemotherapy from senescence to apoptosis - Ingrid Loison; Adrien Pioger; Sonia Paget; Inès Metatla; OrgaRES Consortium; Audrey Vincent; Corinne Abbadie; Vanessa Dehennaut (Cell Death and Disease)
Abstract The potential use of pro-senescence therapies, known as TIS (Therapy-Induced Senescence), for the treatment of colorectal cancer (CRC) generated significant interest since they require lower doses compared to those required for inducing apoptosis. However, the senescent cell cycle-arrested cancer cells are long-lived, and studies have revealed escape mechanisms contributing to tumor recurrence. To deepen our understanding of the survival pathways used by senescent cancer cells, we delved into the potential involvement of the hexosamine biosynthetic pathway (HBP). HBP provides UDP-GlcNAc, the substrate for O-GlcNAc transferase (OGT), which catalyzes O-GlcNAcylation, a post-translational modification implicated in regulating numerous cellular functions and aberrantly elevated in CRC. In this study, we demonstrated, in the p53-proficient colon cancer cell lines HCT116 and LS174T, that TIS induced by low-dose SN38 or etoposide treatment was accompanied with a decrease of GFAT (the rate limiting enzyme of the HBP), OGT and O-GlcNAcase (OGA) expression correlated with a slight reduction in O-GlcNAcylation levels. Further decreasing this level of O-GlcNAcylation by knocking-down GFAT or OGT redirected the cellular response to subtoxic chemotherapy doses from senescence to apoptosis, in correlation with an enhancement of DNA damages. Pharmacological inhibition of OGT with OSMI-4 in HCT116 and LS174T cells and in a patient-derived colon tumoroid model supported these findings. Taken together, these results suggest that combing O-GlcNAcylation inhibitors to low doses of conventional chemotherapeutic drugs could potentially reduce treatment side effects while preserving efficacy. Furthermore, this approach may increase treatment specificity, as CRC cells exhibit higher O-GlcNAcylation levels compared to normal tissues.